Adaptive features selection and EDNN based brain image recognition on the internet of medical things. (October 2022) - Vankdothu, Ramdas; Hameed, Mohd Abdul
Abstract: A brain tumor is one of the fundamental explanations behind fatality among different sorts of malignant growth; the brain is a touchy, intricate, and focal part of the body. The appropriate and convenient conclusion can deflect the life of an individual somewhat. Subsequently, inside this research study, we proposed a brain tumor classification design to consolidate Adaptive Feature Selection and Entropy-based Deep Neural Network (EDNN) based brain image recognition on the Internet of Medical Things (IOMT). The framework regularly contains four modules pre-processing, including extraction, feature selection or determination, and tumor classification. Primarily, we take out the commotion that is noise from the image. The de-noised image is moved to the skull stripping for the brain region extraction. Afterward, the functional features, such as SFTA, geometric, and LBP, are extracted from pre-processed release images. Select the best features using the Adaptive Grill Herd (AKH) Learning Optimization algorithm. Finally, the proposed EDNN classifies brain images as normal brain or abnormal brain based on the extracted features. The EDNN classifier is modified with entropy-based normalization to mitigate the excess overlap inside the neural network's deeper layer towards the maximum pooling layer. Experimental grades demonstrate that the proposed scheme achieves enhanced results compared to the obtainable strategies.